Analisis Efektivitas Penggunaan Sistem Pengarsipan Surat dalam Meningkatkan Efisiensi Kerja di Kantor Ma Laboratorium UINSU - Mely Sintya; Mutiara Quraini Batubara; Sintya Ramadayani; Esa Fakhriyah Lubis; Tengku Darmansah (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study discusses the Analysis of the effectiveness of the use of a letter archiving system in improving work efficiency in the Mal Uinsu office. The purpose of this study was to determine the use of a letter archiving system in improving work efficiency in the Ma laboratory Uinsu office and what obstacles were faced. The results of the study indicate that the implementation of the archiving system in supporting work efficiency at the UINSU Laboratory Madrasah Aliyah includes storage, organization, borrowing, rediscovery, maintenance and destruction. The implementation of this archiving has been running quite well according to existing provisions. However, there are still some things that do not support work efficiency that must be fixed in order to facilitate the implementation of letter archiving in improving work efficiency at the UINSU Laboratory Madrasah Aliyah office.